Comparative Experimental Analysis of Load Carrying Capability of Air Foil Thrust Bearing for Different Configuration of Foil Assembly. (2016) - Ravikumar, R.N.; Rathanraj, K.J.; Kumar, V. Arun
Abstract: Foil bearings are self-acting (aerodynamic) hydrodynamic bearings supports lightly loaded shafts with major advantages like physically non-contacting high speed operation using process fluid as medium in hostile environments. However, the lack of load carrying capacity at relatively lower speeds limits their applications in heavy turbo machinery and as such are highly suitable in lightly loaded, high speed turbo machinery like small gas turbines. This paper discusses the design and assessment of dynamic characteristics in terms of load carrying capabilities as a function of speed, gap between the bearing and the runner as well as shape of foils for an air foil thrust bearing. The effects of various bearing parameters like foil thickness, number of foils fixed circumferentially, foil geometry configuration and position of foils along the circumference such that inner edge and outer edge of the same foil are at different height and same height. Characteristics of performance defined essentially in terms of load carrying capabilities and static stiffness have been used for evaluation. Experiments were conducted for sector foils (with inner edge height less than outer edge height) and sector foils (with inner edge height is equal to outer edge height) by varying number of foils. Along with the above two types the load carrying capabilities of air foil thrust bearing using newly conceptualized cascaded foils (Patented) with increased number of wedge films essentially from the point view of increased pressure profile culminating in relatively higher load carrying capabilities as compared to other two types (conventional) Air foil thrust bearing. The experimental results show that the effect of foil assembly, number and improved formation of wedge film which enhances the load carrying capabilities of air foil thrust bearing. Along with the above experimental work an COMSOL model of the thrust bearing have been analysed to know that the pressure distribution profile on the foil which clearly indicates that the pressure developed by the conventional type of foils configuration is less than the newly configured foils in which inner edge height is equal to outer edge along the radial direction i.e the height of the foil with respect to the runner is equal in the radial direction.